1979
DOI: 10.1084/jem.150.6.1520
|View full text |Cite
|
Sign up to set email alerts
|

The receptor specificity of alloreactive T cells. Distinction between stimulator K, I, and Dr Products and degeneracy of third-party H-2 recognition by low-affinity T cells

Abstract: The specificity of binding of stimulator-derived H-2 antigens by mixed lymphocyte culture (MLC)-activated T blasts was investigated under conditions of antigen excess. We have shown that the detectable proportion of alloantigen-binding blasts from primary MLC is a function of antigen concentration, and can represent up to more than 90 percent of total blasts, when the antigen is presented in the appropriate form (on mitomycin-treated viable stimulator cells, or membrane vesicles prepared from lipopolysaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1981
1981
1988
1988

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 41 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…Such an interpretation also requires that initial priming involve presentation of shed allogeneic class I molecules on I-C + Ts host cells, since the original priming cells are fully H-2 allogeneic. Shedding of MHC determinants (26) and reorientation and recognition of these shed alloantigens on host cells have been documented by others (27)(28)(29).…”
mentioning
confidence: 99%
“…Such an interpretation also requires that initial priming involve presentation of shed allogeneic class I molecules on I-C + Ts host cells, since the original priming cells are fully H-2 allogeneic. Shedding of MHC determinants (26) and reorientation and recognition of these shed alloantigens on host cells have been documented by others (27)(28)(29).…”
mentioning
confidence: 99%
“…Nagy, unpublished results). Thus the antiserum appears to recognize low affinity receptors for H-2k that are expressed by a large proportion of primary MLR blasts [17]. In this report it is demonstrated that the very same 5936' anti-H-2k receptors are expressed on H-2k T cells recognizing antigen in an MHC-restricted fashion.…”
Section: Introductionmentioning
confidence: 91%
“…To remove passively bound stimulator antigens [17,201 and self-Ia antigens [8,91, the cells were treated with trypsin, and incubated overnight in fresh medium containing IL2 (see Sect. 2.6).…”
Section: Binding Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Without washing, 1 volume of selected nontoxic rabbit serum (diluted 3 : 11 in medium) was added and the incubation continued for 60 min at 37°C. The cells were then washed, counted, and their viability was detrmined by fluorescein diacetate staining [14].…”
Section: Depletion Of Ctl With Antisera and Cmentioning
confidence: 99%